1993
DOI: 10.1002/bjs.1800800433
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid tumours of the appendix in children 1957–1986: Incidence, treatment and outcome

Abstract: Forty carcinoid tumours of the appendix were identified in children under 15 years of age between 1957 and 1986 from the records of the West Midlands Regional Children's Tumour Research Group. A significant excess of girls was observed (P = 0.02). All tumours were discovered incidentally and two patients underwent further surgery. Twenty-two of the 29 confirmed locations (76 per cent) were at the tip of the appendix and 34 of the 40 tumours (85 per cent) had invaded beyond the appendiceal submucosa. The report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 10 publications
2
77
0
2
Order By: Relevance
“…Indeed, in the Surveillance, Epidemiology and End Results (SEER) series, only neoplasms considered as malignant are included, with aNENs displaying a very low prevalence (McCusker et al 2002). However, in the paediatric series where NENs are extremely uncommon, aNENs represented the second most common type of GI-NEN (Parkes et al 1993, Corpron et al 1995, Bethel et al 1997, Scott & Upadhyay 2011.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the Surveillance, Epidemiology and End Results (SEER) series, only neoplasms considered as malignant are included, with aNENs displaying a very low prevalence (McCusker et al 2002). However, in the paediatric series where NENs are extremely uncommon, aNENs represented the second most common type of GI-NEN (Parkes et al 1993, Corpron et al 1995, Bethel et al 1997, Scott & Upadhyay 2011.…”
Section: Epidemiologymentioning
confidence: 99%
“…In both adults and children, aNENs are usually diagnosed incidentally, during or after surgical treatment for acute appendicitis or other abdominal conditions (Moertel et al 1990, Parkes et al 1993, Corpron et al 1995, Bethel et al 1997, Plockinger et al 2008, Scott & Upadhyay 2011, Pape et al 2012. The rate of aNENs presence in patients undergoing appendicectomy is reported to be 0.3-0.9% (Moertel et al 1968, Connor et al 1998, Tchana-Sato et al 2006, Debnath et al 2008, In't Hof et al 2008, Shapiro et al 2010, Yilmaz et al 2013; however, in some series, it has been reported to be as high as 2.3% (Hatzipantelis et al 2010, Ozer et al 2011, Van Gompel et al 2007 or as low as 0.16% (Coskun et al 2006, Doede et al 2000.…”
Section: Epidemiologymentioning
confidence: 99%
“…Mesoappendix invasion is a debated variable (MacGillivray et al 1992, Rossi et al 2003. Series with sufficiently long follow-up, including children with a median age of 12 years, revealed that no patient treated by appendectomy died of appendiceal NETs with a diameter below 2 cm (Parkes et al 1993, Stinner et al 1996. A NEC, as part of a mixed exocrine-endocrine carcinoma, has only been reported once so far .…”
Section: Appendixmentioning
confidence: 99%
“…In the 75% of cases the tumor is localized at the apex of the appendix, in 20% and 5% affects the mid portion and the base respectively and discovered accidentally during appendectomy [10]. In children the tumor is usually smaller than 2 cm in diameter [11].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of appendiceal carcinoids is similar to that of acute appendicitis, with intermittent abdominal pain or pain localized in the right lower adominal quadrant, without simultaneously excluded and symptoms of carcinoid syndrome (flushing , bronchospasm , diarrhea , weight loss) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%